Analisa Kekuatan Bahan Komposit Yang Diperkuat Serat Bambu Menggunakan Resin Polyester Dengan Memvariasikan Susunan Serat Secara Acak Dan Lurus Memanjang - Rokki Manurung; Sutan Simanjuntak; Jesayas Sembiring; Suriady Sihombing; Richard A M Napitupulu (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2020)
Composites are materials which are mixed with one or more different and heterogeneous reinforcement. Matrix materials can generally be polymers, ceramics and metals. The matrix in the composite serves to distribute the load into all reinforcing material. Matrix properties are usually ductile. The reinforcing material in the composite has the role of holding the load received by the composite material. The nature of the reinforcing material is usually rigid and tough. Strengthening materials commonly used so far are carbon fiber, glass fiber, ceramics. The use of natural fibers as a type of fiber that has advantages began to be applied as a reinforcing material in polymer composites. This study seeks to see the effect of the use of bamboo natural fibers in polyester resin matrix on the strength of polymer composites with random and straight lengthwise fiber variations. From the tensile test results it can be seen that bamboo fibers can increase the strength of polymer composites made from polyester resin and the position of the longitudinal fibers gives a significantly more strength increase than random fibers.